Experiences of childhood, intimate partner, non-partner, and hate crime-related violence among a sample of people living with HIV in the epicenter of the U.S. HIV epidemic - Sales, Jessica M.; Anderson, Katherine M.; Livingston, Melvin D.; Garbarino, Sophia; Hadera, Selaem; Rose, Eve S.; Carlson, Madelyn S.; Kalokhe, Ameeta S. (Frontiers in Public Health, 2024)
Introduction: Experiences of violence among people living with HIV (PLWH) are thought to be highly prevalent but remain inadequately captured. As a first step toward acceptable, trauma informed practices that improve engagement and retention in care for PLWH, we must acquire more comprehensive understanding of violence experiences. We examined experiences of various forms of lifetime violence: adverse childhood experiences (ACES), intimate partner violence (IPV), nonpartner violence (NPV), and hate crimes among diverse sample of PLWH in Atlanta, Georgia.Methods: Cross sectional data collected from in-and out-of-care PLWH (N = 285) receiving care/support from Ryan White Clinics (RWCs), AIDS Service Organizations (ASOs), or large safetynet hospital, February 2021-December 2022. As part of larger study, participants completed interviewer-administered survey and reported on experiences of violence, both lifetime and past year. Participant characteristics and select HIV-related variables were collected to further describe the sample. Univariate and bivariate analyses assessed participant characteristics across types of violence.Results: High prevalence of past violence experiences across all types (ACES: 100%, IPV: 88.7%, NPV: 97.5%, lifetime hate crimes 93.2%). People assigned male at birth who identified as men experienced more violence than women, with exception of non-partner forced sex. Participants identifying as gay men were more likely to have experienced violence.Conclusion: Among our sample of PLWH at the epicenter of the United States HIV epidemic, histories of interpersonal and community violence are common. Findings emphasize need for RWCs, ASOs, and hospital systems to be universally trained in trauma-informed approaches and have integrated onsite mental health and social support services.